Pre-eclampsia and branch retinal artery occlusion in a 29-year-old primigravida with type 1 diabetes: A case report - Katerina Tori ScB; William Wirostko; Anna Palatnik; Timothy Klatt (Elsevier, 2024)
Branch retinal artery occlusion is a rare cause of sudden vision loss. New-onset visual disturbances are considered a severe feature of preeclampsia and an indication for delivery regardless of gestational age. This report describes the management of a primigravida at 31 weeks of gestation, with multiple comorbidities, who presented with preeclampsia and a new dark spot in her vision. After extensive workup, her branch retinal artery occlusion was not attributable to her preexisting comorbidities nor an undiagnosed thrombophilia. Multidisciplinary collaboration and close observation enabled delay of delivery until 34 weeks of gestation without detriment and substantially mitigated the risks of preterm birth. Her visual defect was stable and permanent. This seems to be the first case in the literature to describe branch retinal artery occlusion diagnosed simultaneously with preeclampsia in the third trimester. Branch retinal artery occlusion may not be a severe feature of preeclampsia requiring delivery.